Estética e política : o cinema outsider de Jim Jarmusch - Pacheco, Helena Lukianski (2021)
This dissertation is a study on the relationship between aesthetics and politics in the filmography of Jim Jarmusch, an exponent filmmaker in American independent cinema. Jarmusch built a unique critical view of the American way of life throughout his career. The methodology film analysis (AUMONT; MARIE, 2009) will be used to investigate how his films compose contrapositions with the “model images” (CUNHA, 2017) of the American way of life and represent outsiders’ ways of life (BECKER, 2009). The methodology will also be applied to investigate how the empty spaces (DELEUZE, 1990) in his films work as a formal-artistic device (KING, 2005). In the political perspective, this choice operates as a way of opposing the neoliberal subjectivity (DARDOT; LAVAL, 2016) that began to strengthen in the 1980s. It is a critical model that has an efficacy that passes through the aesthetic distance, as described by Jacques Rancière in The Emancipated Spectator (2012). Besides, it is observed that the narratives analyzed represent the American nation in its complexity of imagined community (ANDERSON, 1989), beyond the media projection of hegemonic discourses on the American way of life.